The Potential of Aren (Arenga pinnata (Wurmb) Merr.) Stands in Cimantaja Resort, Mount Halimun Salak National Park - Purba, Michael Yohansen; Zuhud, Ervizal A.M.; Bahruni (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
An abundance of palm trees can be found in the Cimantaja Resort Area, where all stands in Cimantaja's Resort are stands that grow naturally/wildly, and without any planting or cultivation activities. This is the aim of this study to estimate the potential of oil palm stands on their productivity. The methods used in estimating the potential in question are interviews and standing inventory. This research was able to show that there was a large potential for stands from the level of poles and unproductive trees with a percentage of 84% being productive trees. In the standing inventory, the regeneration level decreased in value starting from the seedling level to the trees with the sustainable category. Stand productivity in terms of age and time class, the total potential for palm sugar from the 4 largest villages is in the class of age 12-15 class year of 100,933 kg/year with 189 trees, but the total production from a range of age aren, 8-11 class year has percentage of 56% contribute all of the yields.The conclusion of this study stated that Aren has a large potential for stands to be utilized and able to support the economy of aren farmers in the future which of course needs to be supported by the treatment and knowledge of farmers about palm tree cultivation